Implementasi Penyaluran Dana Bantuan Langsung Tunai bagi UMKM pada Masa Pandemi di Kota Tangerang Selatan - Lubis, Annisa Lokita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Direct Cash Assistance (BLT) is one of the government's efforts to save the society's economy. This is not a new thing that the government uses as a policy solution that can be issued quickly when the economy is in an emergency. As during the COVID-19 pandemic that has hit Indonesia since March 2020, the government has implemented one of the BLT programs, namely Assistance for Micro Business Entrepreneurs (BPUM) through the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 2 of 2021 concerning Amendments to Regulation of Minister of Cooperatives, Small and Medium Enterprises Number 6 of 2020 concerning General Guidelines for Distribution of Government Assistance for Micro Business Entrepreneurs to Support National Economic Recovery in Facing Threats That Endanger the National Economy and Rescue the National Economy during the Corona Virus Disease 2019 (COVID-19) Pandemic. The program, which runs from 2020 to 2021 and is planned to be continued in 2022, is expected to be able to maintain the people's economy starting from micro-enterprises which will have an impact on the national economy. This research journal was written to study the effectiveness of the BPUM program procurement in South Tangerang City by analyzing the regulations in force and interviewing with the Head of the Technology and Innovation Section of the Innovation and Technology Data Division of the Cooperatives and Small and Medium Enterprises Office of South Tangerang City. The result is that the program has not run effectively due to the lack of coordination between the center and the regions in implementing the BPUM program.